Triggering factors for allergic conjunctivitis in children and adolescents: scope review protocol (Research, Society and Development, 2022)
Objective: To map the triggering factors of allergic conjunctivitis in children and adolescents. Method: Scope review protocol, registered in the Open Science Framework with no. osf.io/5q3fn and conducted from the Joanna Briggs Institute manual, through the steps: Elaboration of the research question; Construction of the review protocol; Search of publications in the databases; Selection of articles; Extraction of data from articles and Synthesis and Analysis of data. The extension of the PRISMA-ScR checklist was used to search and select articles, using Descriptors in Health Science and Medical Subject Headings, in the LILACS databases, via the Virtual Health Library, MEDLINE, via PubMed, Web of Science and ScienceDirect. The search in the gray literature will be carried out via the Brazilian Digital Library of Theses and Dissertations, Google Scholar and Open Gray. Studies with children (up to 10 years old) and adolescents (10 to 19 years old) that address triggering factors of allergic conjunctivitis will be considered as inclusion criteria. The selection of studies will be carried out by two independent researchers. The articles will be organized within the Mendeley software and the results will be presented in tables, with subsequent narrative discussion.